Remuneração variável e desempenho corporativo: um estudo das empresas brasileiras de capital aberto no período de 2010 a 2017 - Juliana Ribeiro Souza (2019)
Companies, in general, aim to maximize their value, and consequently the wealth of their owners. However, in the context of organizations where ownership and control are separated, conflicts of interest may arise between managers and owners that hinder the achievement of this objective. In this sense, executive compensation and incentive plans are identified as tools that can be used to minimize the problems of existing agencies in organizations, characterized as mechanisms of corporate governance, that is, means of controlling and directing actions according to objectives. translating strategies into procedures and aligning efforts to improve organizational performance. Therefore, the present study aimed to verify the relationship between executive variable remuneration and the corporate performance (financial and market) of publicly traded Brazilian companies in the period from 2010 to 2017.The executives were considered as the sum of the members of the Board of Directors (BD), the Statutory Directorate (SD) and the Fiscal Council (FC) of each company. The sample consisted of 229 companies listed in B3, from nine economic sectors. The results showed that the past return positively influences the current return of companies; that the lower the level of leverage, the greater the company's profitability, and consequently the better its operating performance; the economic recession caused a reduction in the financial performance of the companies analyzed; that the fixed assets index positively affects the growth of companies and the return on shares; and that companies with higher market shares have better market performance. In addition, the variable remuneration proxies were not statistically significant in any of the financial performance models. There was a statistically significant relationship between variable remuneration and performance only in the market performance model for return on shares (RET), in which the Total Variable Remuneration (RVT) at t=0 was negatively related to RET, and positively related to it when analyzed at t + 1. In such a way, it was concluded that the relationship between the variable remuneration of the executives and the corporate market performance of publicly traded Brazilian companies occurs in a bidirectional way.